Psychological Meaningfulness and Contextual Performance: Mediation Role of Employee Engagement - Cudjor, Samuel Kwesi; Arkaifie, Samuel Jabez; Opata, Grace (JURISMA : Jurnal Riset Bisnis & Manajemen, 2024)
Research has increasingly focused on psychological factors that enhance employee engagement and improve outcomes. While prior studies have shown a positive link between psychological meaningfulness and contextual performance, the mediating role of employee engagement in this relationship remains underexplored. This study investigated the connections between psychological meaningfulness, employee engagement, and contextual performance. Specifically, it examined how psychological meaningfulness influences contextual performance, the impact of psychological meaningfulness on employee engagement, and the effect of employee engagement on contextual performance. Data from 380 nurses in Ghana were analyzed using PLS-SEM 3. The results revealed that psychological meaningfulness significantly enhances both employee engagement and contextual performance. Moreover, employee engagement was positively linked to contextual performance and served as a significant mediator in the relationship between psychological meaningfulness and contextual performance. These findings suggest that organizations should prioritize psychological meaningfulness to foster employee dedication and enthusiasm, which, in turn, boosts job performance and participation in activities benefiting both individuals and the organization Keywords: Contextual Performance; Employee Engagement; Employee Engagement Theory; Nurses; Psychological Meaningfulness